Frequent Episodes of Detectable Viremia in HIV Treatment-Experienced Children is Associated with a Decline in CD4+ T-cells Over Time. - Paintsil, Elijah; Martin, Ryan; Goldenthal, Ariel; Bhandari, Shreya; Andiman, Warren; Ghebremichael, Musie (Journal of AIDS & clinical research, 2016)
The clinical consequences of the magnitude and the duration of detectable viremia in HIV-infected children have not been well characterized. We examined the predictors and immunologic consequences over time of frequent episodes of detectable viremia in HIV-infected children followed at Yale-New Haven Hospital.